Peningkatan Kapasitas Kemampuan Bahasa Inggris Bagi Pemandu Ekowisata Gunung Api Purba Nglanggeran - Muhammad Dzulkifli; Andreas Yogi Prasetyo; Sucipto (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2022)
The Nglanggeran Ancient Volcano area or also known as the Nglanggeran Tourism Village has a lot of good reputation and achievements at national and international levels. It has made many foreign tourists interested in visiting since 2009 until now. Human resources in the service sector, especially the guide, need to be improved, especially in delivering and serving information in English. The aim of this community service activity is to improve the ability of the guides to communicate in English. The method was in a cycle of need analysis, design, implementation and evaluation. As a result, 6 out of 10 participants who participated intensely in the training were stated to be able to communicate quite smoothly and be able to respond to questions from foreign tourists. In addition, Nglanggeran Tourism Village can provide local guides in foreign languages if foreign guests visit.